The effect of calcium on calcium oxalate monohydrate crystal-induced renal epithelial injury - Khaskhali, Muhammad H. (2008)
Since hypercalciuria is a common feature of idiopathic calcium oxalate (CaOx) nephrolithiasis, renal epithelial cells of stone patients are exposed to various crystals in the presence of high calcium. This study was performed to determine the effect of high calcium levels on CaOx crystal-induced cell injury. We exposed human renal epithelial cell line, HK2 in vitro to CaOx monohydrate crystals at a concentration of 133 μg/cm(2) for 1, 3, 6 or 12 h in the presence or absence of 5 or 10 mM/L calcium Ca(++). We determined the release of lactate dehydrogenase as marker of injury and hydrogen peroxide (H(2)O(2)) and 8-isoprostane (8-IP) as sign of oxidative stress. Cells were also examined after trypan blue and nuclear DNA staining with 4′,6-diamidino-2-phenylindole to determine their membrane integrity and apoptosis respectively. Exposure of cells to 5 or 10 mM/L of Ca(++,) for up-to 6 h, resulted in increased trypan blue and DAPI staining and production of H(2)O(2). Similarly an exposure to CaOx crystals also resulted in increased trypan blue and DAPI staining and H(2)O(2) production. An exposure to 5 mM/L Ca or CaOx crystals also resulted in increased production of 8-IP. A combination of the two treatments, Ca and CaOx crystals, did not show anymore changes than exposure to high Ca or CaOx crystals alone, except in the case of a longer exposure of 12 h. Longer exposures of 12 h resulted in cells sloughing from the substrate. These results indicate that exposure to high levels of Ca or CaOx crystals is injurious to renal epithelial cells but the two do not appear to work synergistically. On the other hand, results of our earlier studies suggest that oxalate and CaOx crystals work in synergy, i.e., CaOx crystals are more injurious in the presence of high oxalate. Perhaps Ox and CaOx crystals activate different biochemical pathways while Ca and CaOx crystals affect the identical pathways.